2020
DOI: 10.1021/acs.analchem.0c03010
|View full text |Cite
|
Sign up to set email alerts
|

A Light-Up Strategy with Aggregation-Induced Emission for Identification of HIV-I RNA-Binding Small Molecules

Abstract: Fluorescence methods are important tools to identify RNA-binding small molecules and further employed to study RNA–protein interactions. Most reported fluorescence strategies are based on covalent labeling of ligand or RNA, which can impede the binding between them to some extent, or light-off fluorescent indicator displacement methods, which ask for particular indicators. Herein, a label-free fluorescence strategy based on the light-on aggregation-induced emission (AIE) feature of tetraphenylethene (TPE) deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Various aptamers now can be routinely engineered through repeated rounds of in vitro selection, also known as systematic evolution of ligands by exponential enrichment (SELEX), the powerful technique that was developed in the early 1990s. , Since then, numerous different types of aptamers against different target molecules have been selected in academic research laboratories and have found applications in various biotechnological fields. In particular, the fluorogenic RNA aptamers are known for their specificity in binding otherwise nonfluorescent dyes; the fluorescent emission of the dye is activated only upon binding to its RNA aptamer. This binding specificity enabled the design not only of label-free nucleic-acid-based sensors in vitro but also the attractive development of binary 1 and 0 systems, as shown in Figure D,E. , The input signal induces the conformational change of the fluorophore-binding pocket (analogous to a “gate”), dictating the overall affinity strength of the RNA–fluorophore complex. Various factors can potentially serve as inputs, including single-stranded oligonucleotides and nonfluorescent molecules mimicking structures of the ligand dye.…”
Section: On Dynamic Structures and Logic Gatingmentioning
confidence: 99%
“…Various aptamers now can be routinely engineered through repeated rounds of in vitro selection, also known as systematic evolution of ligands by exponential enrichment (SELEX), the powerful technique that was developed in the early 1990s. , Since then, numerous different types of aptamers against different target molecules have been selected in academic research laboratories and have found applications in various biotechnological fields. In particular, the fluorogenic RNA aptamers are known for their specificity in binding otherwise nonfluorescent dyes; the fluorescent emission of the dye is activated only upon binding to its RNA aptamer. This binding specificity enabled the design not only of label-free nucleic-acid-based sensors in vitro but also the attractive development of binary 1 and 0 systems, as shown in Figure D,E. , The input signal induces the conformational change of the fluorophore-binding pocket (analogous to a “gate”), dictating the overall affinity strength of the RNA–fluorophore complex. Various factors can potentially serve as inputs, including single-stranded oligonucleotides and nonfluorescent molecules mimicking structures of the ligand dye.…”
Section: On Dynamic Structures and Logic Gatingmentioning
confidence: 99%
“…Previous work introduced the TPE derivative into the HIV-I TAR RNA−Tat peptide system as a fluorescent indicator. 23 However, the fluorescence signal is easily interfered with by test ligands in the homogeneous reaction system. Here, a TPE derivative was used to label the Tat peptide as a fluorescent indicator in a separable system to study the TAR RNA−Tat peptide interactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The introduction of TPE derivatives to monitor RNA–protein interactions has aroused great interest in us. Previous work introduced the TPE derivative into the HIV-I TAR RNA–Tat peptide system as a fluorescent indicator . However, the fluorescence signal is easily interfered with by test ligands in the homogeneous reaction system.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from oligonucleotide therapeutics, the discovery of small molecules that bind to RNAs and regulate their functions is highly desirable in drug discovery of RNA-targeted small molecules. [7][8][9] Researchers have focused on the exploratory study of RNA-targeted small molecules utilizing various screening methods such as the fluorescent indicator displacement (FID) assay, [10][11][12][13][14][15] small molecule microarray-based screening, [16][17][18] affinityselection mass spectroscopy, 19,20 surface plasmon resonance (SPR)-based screening, 21 in silico screening, 22 fragment-based screening, [23][24][25] and DNA-encoded library technology. 26,27 The FID assay is a simple and high-throughput method that can detect the interactions between small molecules and RNAs without fluorescent labelling of both target RNAs and compounds used in screening.…”
mentioning
confidence: 99%
“…An FID assay has been used to screen small molecules targeting various structured RNAs including bacterial rRNA A-site, HIV-1-TAR, Rev response element, enterovirus RNA structure, and disease-causing repeat RNAs. [10][11][12][13][14][15]29,30 Since fluorescent indicators used in RNA-targeted FID assays bind to secondary structures including hairpins, bulges, and internal loops with low sequence selectivity, screening of RNA-binding small molecules based on the displacement of non-selective fluorescent indicators may lead to a decrease of the accuracy in FID assays. Therefore, the development of fluorescent indicators that selectively bind to target RNAs could provide a rigorous screening system with high accuracy.…”
mentioning
confidence: 99%